ANALISIS KUALITAS PELAYANAN DI PERPUSTAKAAN UMUM KABUPATEN BOYOLALI - Naning Choiri Nisa Rachma; Herbasuki Herbasuki (Journal of Public Policy and Management Review, 2020)
The term administration for public implies that the government as the organizer of public services has the duty to provide public services in accordance with public’s needs. The Regional Government of Boyolali has organized various types of public services, one of them being the Public Library of Boyolali which is actively providing information services. Public library as one of the provider of information services that is accessible for all community members, can be the link between the high price of books and the increasing needs for information inside the community. The role of public libraries in increasing visitors’ knowledge will be achieved if the library capable of providing a good quality service to its visitors. The purpose of this study is to analyze the services quality in the Public Library of Boyolali and also the factors influencing service quality at the Public Library of Boyolali. This study uses the theories of Zeithaml and Satoh et al consisting of Tangible, Reliable, Responsiveness, Assurance, Empathy, and Collection and Access, factors that influence the service quality use theories from Moenir and Thoha consisting of service facility and system factors, GAP Model, and Importance Performance Analysis (IPA). This study is a quantitative research with descriptive method. The study population was the whole visitors of the Public Library of Boyolali and using incidental sampling techniques with 92 respondents. The results showed that the overall service in the Public Library of Boyolali has an average level of performance on 2.76 and an average level of importance on 3.62 means that the service is considered to be good.